Pengaruh Stretching Exercise Terhadap Konsentrasi Belajar pada Siswa di SDN 02 Jaten - Nanda Putri; Eska Dwi Prajayanti (Yayasan Literasi Sains Indonesia, 2022)
Learning concentration is the ability to focus on the lesson. When a person's concentration decreases, a person, especially a student, will do activities that should not be done, such as falling asleep during class hours, chatting to themselves, and playing games that cause the learning process to be ineffective. One activity that has the opportunity to increase learning concentration is the provision of stretching exercises so that the learning process becomes effective and conducive. Stretching exercises are necessary muscle stretches and are used for both healthy and sick people to stretch, flex or increase the flexibility of muscles that are considered problematic. To determine the effect of stretching exercise on the concentration of learning in students. The research design is Quasi Experiment with One Group Pretest-posttest Design research design. Sampling of 49 respondents. The research instrument used was SOP stretching exercise and learning concentration questionnaire. Data analysis using Wilcoxon test. The results showed a significant value of stretching exercise on learning concentration in students with p value 0.000 <0.05. There is an effect of stretching exercise on learning concentration in students of SDN 2 Jaten.